Development of quinone-rich fraction of Ardisia crispa (Thunb.) A.DC roots mitigates rheumatoid arthritis by suppressing angiogenesis, in vitro and in vivo - Blin, Joan (2021)
Angiogenesis, a process of new blood vessel formation from pre-existing ones, can perpetuate synovial inflammation and joint destruction at its equivocal balance in rheumatoid arthritis (RA). Targeting excessive angiogenesis underlies the early development of RA, a chronic autoimmune joint condition, has therefore become a promising approach for the disease intervention. Limitations of current arthritis therapies have encouraged for rapid development of alternative adjuncts from natural sources. 2-methoxy-6-undecyl-1,4-benzoquinone (BQ) is a pbenzoquinone derivative of Ardisia crispa roots (Family: Primulaceae), with proven anti-angiogenic properties. However, it is still unclear how BQ is able to inhibit angiogenesis in RA. Hence, this present study investigated the anti-arthritic potential of quinone-rich fraction (QRF) (a rich fraction containing the BQ) from Ardisia crispa roots, targeting angiogenesis inhibition in vitro and in vivo. Preparation of test samples from Ardisia crispa roots using n-hexane, followed by fractionation and isolation via column chromatography, yielded Ardisia crispa roots hexane extract (ACRH) [13.64 g; 24.0%, weight per weight (w/w)], QRF (1.99 g; 14.6%, w/w), and BQ (0.04 g; 1.9%, w/w), respectively. Subsequently, gas chromatography-mass spectrometry (GC-MS) analyses have confirmed the benzoquinonoid content in each sample [ACRH (6.1%, peak-area-percent), QRF (30.5%, peak-area-percent), and BQ (81.4%, peak-area-percent)]. Antiangiogenic and anti-arthritic activities of ACRH, QRF, and BQ were tested via cell viability MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay, tube formation, cell invasion, and cell apoptosis assays in vascular endothelial growth factor (VEGF)-induced human umbilical vein endothelial cells (HUVECs) and interleukin-1β (IL-1β)-induced human fibroblast-like synoviocytes for rheumatoid arthritis (HFLS-RA), respectively. ACRH, QRF, and BQ exhibited a narrow therapeutic range in VEGF-induced HUVECs (IC50=1.09±0.18 μg/mL, 3.85±0.26 μg/mL, and 1.34±0.16 μg/mL) and IL-1β-induced HFLS-RA (IC50=3.60±1.38 μg/mL, 4.47±0.34 μg/mL, and 1.09±0.09 μg/mL), respectively. ACRH, QRF, and BQ at 0.05, 0.5, and 5 μg/mL, respectively, significantly inhibited/suppressed (P<0.05) VEGF-induced HUVEC tube formation and IL-1β- induced HFLS-RA invasion, respectively. Moreover, ACRH and BQ at 5 μg/mL, but not QRF, significantly (P<0.05) enhanced apoptosis of IL-1β-induced HFLSRA. Based on comparable in vitro findings of all samples, QRF was chosen for in vivo studies by employing a collagen-induced arthritis (CIA) model in male adult Sprague-Dawley rats. QRF at daily doses of 3, 10, and 30 mg/kg, insignificantly (P>0.05) reduced the arthritic scores, ankle swelling, and paw edema in arthritic rats after 13 days treatment, respectively. Additionally, at all doses, QRF also showed no significant (P>0.05) modulation on the body weights and organ weights, i.e., liver, kidney, and spleen, respectively. Protein expression analyses using enzyme-linked immunosorbent assay (ELISA) and multiplex assay demonstrated that QRF at all doses (3, 10, and 30 mg/kg) significantly (P<0.05) attenuated VEGF-A, PI3K, AKT, NF-κB, p38, STAT3, and STAT5 proteins level in arthritic rats in a dose-independent manner. QRF at all doses also significantly (P<0.05) restored synovial microvessel densities (MVD) in arthritic rats to the normal level. Notably, a medium dose of QRF (10 mg/kg) exerted the highest inhibition to the aforementioned biomarkers and MVD than other doses. In conclusion, QRF mitigated RA development by suppressing angiogenesis in vitro and in vivo, attributed to the benzoquinonoid content and synergism, at least in part, by other phytoconstituents. Further investigation should identify the unknown peaks in the current GC-MS fingerprinting of QRF to better understand the potential involvement/synergism of other compounds in the sample.